2019
DOI: 10.32598/jccnc.5.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Role Ambiguity and Organizational Justice as the Predictors of Unethical Behavior Among Nurses

Abstract: Background: Unethical behavior among nurses is gradually becoming a severe problem in the health sector of Nigeria, and this calls for urgent concern. However, it may be associated with issues inside healthcare organizations. Therefore, this study aimed to investigate the relationship between role ambiguity, organizational justice, and unethical behavior among nurses. Methods: This was a cross-sectional study. In total, 300 participants were selected from Lagos State Teaching Hospital (LUTH) in Lagos metropoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…For example, in one study conducted in the United States, all 27 nurses who took part in the study had witnessed unethical behavior by nurses, and most had been involved in or were unsure if they had participated in unethical behavior [2]. In African countries, such as Nigeria, unethical behavior among nurses, such as lateness to work, theft, and the misappropriation of funds has recently received much disapproving attention [3]. Iranian nurses also reported witnessing destructive and unethical behavior by their fellow nurses [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one study conducted in the United States, all 27 nurses who took part in the study had witnessed unethical behavior by nurses, and most had been involved in or were unsure if they had participated in unethical behavior [2]. In African countries, such as Nigeria, unethical behavior among nurses, such as lateness to work, theft, and the misappropriation of funds has recently received much disapproving attention [3]. Iranian nurses also reported witnessing destructive and unethical behavior by their fellow nurses [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one study conducted in the United States, all 27 nurses who took part in the study had witnessed unethical behavior by nurses, and most had been involved in or were unsure if they had participated in unethical behavior [ 2 ]. In African countries, such as Nigeria, unethical behavior among nurses, such as lateness to work, theft, and the misappropriation of funds has recently received much disapproving attention [ 3 ]. Iranian nurses also reported witnessing destructive and unethical behavior by their fellow nurses [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…51,52 Organizational justice and unethical behavior by nurses are correlated. 53 In the studies conducted in Iran and Egypt, organizational justice perceived by nurses was reported to be lower than average, which was associated with deviance in the work environment. 54,55 Considering the effect of organizational justice on the quality of care provided to patients, nursing managers can help maintain and create a healthy and supportive work environment for nurses and improve care quality by planning to reduce discrimination and promote organizational justice.…”
Section: Discussionmentioning
confidence: 99%